2015
DOI: 10.1053/j.gastro.2015.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Portal Venous Circulating Tumor Cells From Patients With Pancreaticobiliary Cancers by Endoscopic Ultrasound

Abstract: BACKGROUND & AIMSTumor cells circulate in low numbers in peripheral blood; their detection is used predominantly in metastatic disease. We evaluated the feasibility and safety of sampling portal venous blood via endoscopic ultrasound (EUS) to count portal venous circulating tumor cells (CTCs), compared with paired peripheral CTCs, in patients with pancreaticobiliary cancers (PBCs).METHODSIn a single-center cohort study, we evaluated 18 patients with suspected PBCs. Under EUS guidance, a 19-gauge EUS fine needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 34 publications
6
116
0
Order By: Relevance
“…Compared to other types of cancer, pancreatic cancer produces fewer CTCs in peripheral blood, evidenced by the lowest number of CTCs detected per unit of blood in PC among 12 different cancer types [24]. Catenacci et al have reported that significantly more CTCs were detected in the portal vein blood than peripheral blood (118.4 ± 36.8 CTCs/7.5 mL vs. 0.8 ± 0.4 CTCs/7.5 mL, p<0.1) [25]. Correspondingly, 100% patients were detected to be CTC positive (18 pancreatic cancer patients) with portal vein blood but only 4 out of 18 CTC positive patients were seen in peripheral blood.…”
Section: Diagnostic Values Of Pancreatic Ctcmentioning
confidence: 99%
“…Compared to other types of cancer, pancreatic cancer produces fewer CTCs in peripheral blood, evidenced by the lowest number of CTCs detected per unit of blood in PC among 12 different cancer types [24]. Catenacci et al have reported that significantly more CTCs were detected in the portal vein blood than peripheral blood (118.4 ± 36.8 CTCs/7.5 mL vs. 0.8 ± 0.4 CTCs/7.5 mL, p<0.1) [25]. Correspondingly, 100% patients were detected to be CTC positive (18 pancreatic cancer patients) with portal vein blood but only 4 out of 18 CTC positive patients were seen in peripheral blood.…”
Section: Diagnostic Values Of Pancreatic Ctcmentioning
confidence: 99%
“…Pancreatic venous effluent in the portal venous system is an obvious potential source of large numbers of CTCs in PDAC, and in 2015, Catenacci et al 85 demonstrated that EUS-guided transhepatic aspiration of portal venous blood was safe and yielded relatively large numbers (~ 100 CTCs per 7.5 mL blood) of PDAC CTCs. Further, these CTCs contained the same mutations as seen in regional lymph nodes of patients who later underwent surgery.…”
Section: Eus and New Technologiesmentioning
confidence: 99%
“…EUS-guided sampling of the portal vein flow has been actually proposed to detect circulating tumor cells, with the aim of better selecting patients for chemotherapy or local resections. [33] Local delivery of cytotoxic or even magnetic nanoparticles, based on EUS-guided portal vein injections, has also been envisaged in advanced pancreatic adenocarcinoma with liver metastases. [34]…”
Section: Perspectivesmentioning
confidence: 99%